SIKAP REMAJA DENGAN PEMANFAATAN PIK-R PADA REMAJA - Arum Dwi Anjani; Beril Triana (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
ATTITUDES OF ADOLESCENT USING PIK-R IN ADOLESCENTS Background The problem that stand out among the teenager is problem around Triad KKR (sexuality, HIV and AIDS also NAPZA) based on the visit record to PKPR, found that number of IMS incident to teenager rank first, that is around 50% from the total of counseling that done at 2009.Mention that the rampant cases happens because of prosmicuti that related to reproduction health for teenager. Purpose to know the relation of teenager attitude with utilization of PIK - R to teenager. Methods use